ROLE OF ABHYANGA IN ALPA NIDRA - Dr. Sushil Kumar Sharma, Dr. Pooja Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2017)
Ayurveda is an ancient science of life, which nearly related to life style. In this way if we do not obey life style, so many problems may develop in human body. Nidraconcern as an another term sleep. Sleep is very important phenomenon in an organism and also accepted by modern science because of its restorative function and importance for conservation of energy and growth, so good sleep is best indicator of good health. It affects adversely, if properly not taken by any one and leads to sleep disorders and it is most common complaint in present era. Management of AlpaNidrais been dealt in the form of daily routine i.e., Padabhyanga, medicament and proper lifestyle. KEYWORDS: Nidra, Sleep, Ayurveda, AlpaNidra, Pad abhyanga.